2010
DOI: 10.1111/j.1469-8986.2009.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation and fluid intelligence: Insights from pupillometry

Abstract: Thinking is biological work and involves the allocation of cognitive resources. The aim of this study was to investigate the impact of fluid intelligence on the allocation of cognitive resources while one is processing low-level and high-level cognitive tasks. Individuals with high versus average fluid intelligence performed low-level choice reaction time tasks and high-level geometric analogy tasks. We combined behavioral measures to examine speed and accuracy of processing with pupillary measures that indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
119
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 69 publications
25
119
0
Order By: Relevance
“…Recent work ( Van Der Meer et al, 2010) has indicated that high fluid-intelligence individuals have larger task-evoked pupillary responses when performing difficult tasks. This supports the view that people with high Gf may simply have more cognitive resources that can be recruited during demanding tasks (resource hypothesis; Van Der Meer et al, 2010). Earlier work (Ahern & Beatty, 1979, 1981 showed the opposite pattern in which higher intelligence individuals showed smaller task-evoked pupillary responses than those with average intelligence.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Recent work ( Van Der Meer et al, 2010) has indicated that high fluid-intelligence individuals have larger task-evoked pupillary responses when performing difficult tasks. This supports the view that people with high Gf may simply have more cognitive resources that can be recruited during demanding tasks (resource hypothesis; Van Der Meer et al, 2010). Earlier work (Ahern & Beatty, 1979, 1981 showed the opposite pattern in which higher intelligence individuals showed smaller task-evoked pupillary responses than those with average intelligence.…”
Section: Discussionsupporting
confidence: 64%
“…The control hypothesis offers a parsimonious explanation for the conflicting earlier findings on the relationship between intelligence and pupillary response. In tasks that require exploration (such as the geometric analogy task used by Van Der Meer et al, 2010), highGf individuals who shift into higher gain states will have larger task-evoked pupillary responses than low-Gf individuals. On the other hand, overlearned tasks that primarily require exploitation (such as the mental multiplication, digit span used by Ahern & Beatty, 1979, 1981 are easier for high-Gf than low-Gf individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the VC test, the lights lit up 12 times at different parts of the panel at random intervals. This test requires more processing and is thought to represent the function of the pre-frontal cortex, and this could be considered part of the executive function of the brain [33]. We used the mean values of reaction time on the RT test as an assessment of global cognition and the mean values of reaction time on the VC test as an assessment of executive function.…”
Section: Methodsmentioning
confidence: 99%
“…Using the method of pupillometry (see below), they found individuals of higher cognitive abilities (measured by Scholastic Aptitude Scores) to allocate less resources to three out of the four applied cognitive (i.e., arithmetic and verbal reasoning) tasks. Since then, quite a few studies have been conducted investigating the relationship between general cognitive abilities and the allocation of cognitive resources (e.g., Heitz, Schrock, Payne and Engle 2008;Rypma, Berger, Prabhakaran, Bly, Kimberg et al 2006;van der Meer, Beyer, Horn, Foth, Bornemann et al 2010), but they produced conflicting results. We argue here that some of these results can be reconciled when the characteristics of the tasks are carefully observed.…”
mentioning
confidence: 98%